Comparison of Selected Aspects of English Subject in the New and the Old Secondary Curriculum. - Akugizibwe, Masika Sharon (Kabale University, 2024)
The study was about the Comparison of Selected Aspects of English Subjects in the New and the Old Secondary Curriculum. The study employed the document review as well as interview methods to collect the requisite data. The findings revealed there is a marked difference in terms of the aims and objectives as presented in the old curriculum and the CBC curriculum. This shows that there was indeed a need to revise the old curriculum. The findings further revealed that the teachers were not conversant with the aims and objectives in the CBC curriculum yet they are expected to implement the same. It is possible that such a situation would likely contribute to poor composition writing since teachers teach what they feel they should teach instead of adhering to what is stipulated in the CBC. This is possibly a reflection of the general failure to implement the new curriculum.